Options for governing the microbial commons - Halewood, Michael (2011)
Recent decades have witnessed an ever-increasing range and volume of digital data. All elements of the pillars of science--whether observation, experiment, or theory and modeling--are being transformed by the continuous cycle of generation, dissemination, and use of factual information. This is even more so in terms of the re-using and re-purposing of digital scientific data beyond the original intent of the data collectors, often with dramatic results.